Subject/Keyword Index to Volume 15 (Microscopy and microanalysis, 2009)
(ProQuest: ... denotes non-US-ASCII text omitted.) A Aberration, 441 Absorption contrast, 231 Accuracy, 524 Agglomeration, 130 Alloys, 36 Analysis of layered thin films, 99 Analytical electron microscopy, 99 Anatomy, 166, 194 Anode, 71 Anomalous absorption, 83 Anomalous transmission, 83 Anticancer naturally fluorescent compound in tumor and normal cells, 545 Antifungal activity, 366 Aragonite, 197 Aspergillus niger, 366 Atherosclerosis, 338 Atomic force microscopy, 259 B Bilayers, 99 C Calcite, 197 Calotropis procera, 539 Canine, 2 Carbon, 384 Carbonate biominerals, 197 Carbon-based functional polymer systems, 251 Carbon contamination, 99 Carboniferous, 166 Cathodoluminescence, 222 CBED, 558 Cellulose acetate peel, 166 Channeling, 83 Channels between cork cells, 539 Charge transport, 323 Chemical mapping, 54 Chemical shift, 106 Chiton Acanthopleura hirtosa, 154 Clitoria ternatea, 366 Clitoria ternatea leaf extract, 366 Coherence, 272 Collection efficiency, 93 Complex suspensions, 130 Composition gradient, 62 Computed tomography (CT), 395 Computer-assisted image analysis, 353 Computer-assisted image processing, 353 Conductance band, 125 Confocal microscopy, 545 Connectivity, 71 Continuum, 491 Contrast mechanisms and image formation, 147 Controlled-drift detectors, 231 Copper wire, 244 Cork, 539 Coronary vasculature, 415 Corrosion cast, 194 Cross section, 558 Cryomicroscopy, 130 Cu-Al, 54 CuAl2, 54 Cumulus cells, 2 D DC photoelectron gun parameters, 298 Deconvolution, 491 Detector solid angle formulas, 93 Diffraction enhanced imaging, 231 Diffraction intensity, 197 Digital filter, 491 Diptera, 422 Dopant contrast, 125 Dopant profiling, 237 Dorsal aorta, 194 Drug uptake, 545 Dynamic transmission electron microscopy, 272 E EBSD, 435 EDS, 83, 93, 454, 491 EDS software, 491 EDX, 114 EDXS, 435 EELS, 62, 114, 154, 505, 524 Effect of oxide overlayers, 237 Efferent branchial arteries and splanchnic arteries, 194 EFTEM, 154 Elasmobranch, 194 Electron, 454 Electron channeling, 83 Electron cryotomography, 183 Electron diffraction, 20 Electron diffraction based analysis, 20 Electron emission contrast, 125 Electron energy-loss near-edge structure (ELNES), 106 Electron energy-loss spectroscopy, 54, 213 Electronic structure, 36 Electron microprobe, 222 Electron microscopy, 237, 244, 298 Electron probe microanalysis, 83 Electron probe microanalyzer, 476 Electron sources, 290 Electron tomography, 244, 377 Elemental mapping., 231 ELNES, 505 Emittance, 298 Endocrine pancreas, 345 Energy dispersive spectroscopy, 476, 484 Energy dispersive X-ray spectrometry, 476 Energy filtered transmission electron microscopy (EFTEM), 54 Epibranchial, 194 EPMA, 83, 454 Epoxy, 197 Exocrine pancreas, 345 F 40 years of EDS, 475 FcRn, 183 Fe-Co alloy, 114 Fe-Co alloy nanoparticles, 114 Feline, 2 Femtosecond laser, 323 Ferritin, 154 FET, 484 FIB, 558 FIB-nanotomography, 71 FIB-SEM, 71 Filter-fit, 491 First-principles band structure calculation, 106 Focused ion beam (FIB), 130 Focused ion beam fold-out, 558 Fold-out, 558 Forensic, 189 Fossil, 166 Fractal geometry, 415 Frictional force microscopy, 259 Functional polymer systems, 251 Fungus, 395 Fusarochromanone (FC101), 545 G GaAs, 125 Gadolinium, 338 Gastric arteries, 194 Gold-coated silicon substrates, 30 Granular materials, 130 Growth and morphogenesis of Aspergillus niger, 366 H HAADF-STEM, 46 Hair, 189 Hair color, 189 Hair thickness, 189 He ion microscope, 147 Hemopoietic progenitor cell, 403 Hemopoietic stem cell, 403 Hemopoietic stem cell niche in situ, 403 HfO2, 15 High-angle annular dark field, 251 High-resolution scanning electron microscopy, 125 Homing, 403 HREM, 114 HRTEM, 46 Hyaluronic acid, 403 Hymenoptera, 422 Hyperspectral, 222 I Image analyses, 415 Image analysis, 130, 384, 545 Imaging, 395 Immature phases, 422 Immunogold, 403 Immunohistochemistry, 353 Improved aberration-corrected STEM, 441 Incomplete charge collection, 484 Innovative triple immunogold labeling method, 403 In situ EELS, 204 In situ electron microscopy, 272 Integrated circuit, 244 Interdiffusion, 30 Interface, 106 Interface structure, 213 Interleukin-6, 415 Intermetallics, 36 Iron, 154 K (K,Na)NbO3, 435 Kalgoorlie scheelite, 222 K-factor, 524 Ki-67 antigen, 353 K-ratio, 491 L La0.7Sr0.3MnO3/SrTiO3 (0 0 1) thin film interfaces, 213 Labeling, 183 Lateral force microscopy, 259 Least-squares fit, 491 Line edge roughness, 244 Liposome, 183 Low vacuum scanning electron microscopy, 166 M Macroscopic and microscopic hair color measurements, 189 Macroscopic hair, 189 Magnetic resonance imaging, 338 Magnetite, 154 Management purposes, 422 Mapping, 222 Mediterranean fruit fly, Ceratitis capitata, 422 Metallic multilayers, 54 Microanalysis, 222 Microbeam analysis, 484 Microcantilevers, 259 Microscopic hair, 189 Microscopy, 353 Microstructure, 71 Microstructure of surface and subsurface layers, 62 Microtomography, 384 Microwave, 154 Mn valency, 213 Modeling rectangular cantilevers during torsion and deflection, 259 Monte Carlo, 454 Monte Carlo modeling, 237 Monte Carlo simulation, 99 Multichannel analyzer, 491 Mussel, 197 N Nanocrystalline thin films, 20 Nanocrystals, 20 Nanofabrication, 204 Nanogold, 183 Nanogold as a specific marker, 183 Nanomaterials, 323 Nanometer, 197 Nanoparticles, 114, 130 Nanophosphor, 46 Nanopore, 204 Nanotomography, 130 NbO, 505, 524 NbO2, 505, 524 Nb2O5, 505, 524 Near-edge fine structure, 213 Niche, 403 Nickel-oxide films, 99 Nickel-titanium microwire, 62 Niobium, 505 Niobium and stoichiometric niobium-oxide phases, 505, 524 Niobium oxide, 505, 524 Ni release, 62 Ni-Ti shape memory microwire, 62 Nitrogen K-edge and titanium L3-edge at TiN/Ti interface, 106 Ni-YSZ, 71 Normal cells, 545 Novel radio-frequency gun structures, 290 Nuclear microprobe, 345 Nuclear microscopy, 338, 345 Numerical modeling, 259 O Observing silver-stained osteocytes in situ, 377 Oocyte, 2 Optimizing electron backscatter diffraction, 197 Oral leukoplakia, 353 Ordinary portland cement, 130 Organic matrix, 154 ORION, 147 Osteocyte, 377 Osteopontin, 403 Overvoltage, 83 Oxidation state, 505 Oxide films deposited on silicon wafers, 15 P Particle size distribution, 130 Permeability, 384 Perovskites, 213 Phase fractions, 20 Phellogen, 539 Photoemission, 298 Photon-assisted electron energy loss spectroscopy, 314 Photovoltage, 323 PIXE, 338, 345 Plan-view, 558 Plasmodesmata, 539 Plasmon and near-edges fine structure, 505 Plasmon EELS chemical mapping, 54 Plasmon mapping, 54 Porosity, 384 Precision, 524 Preimaginal phases and development of Pachycrepoideus vindemmiae, 422 Projection measurements, 244 Pteridosperms, 166 Pteromalidae, 422 Pump-probe microscopy, 314 Q Quantification, 222, 524 Quantitative analysis, 20 Quantitative cathodoluminescence mapping, 222 Quantitative evaluation of immunohistochemistry in pathology, 353 Quantitative imaging of gadolinium distribution within tissue sections, 338 Quantum wells, 125 Quantum wells in GaAs p-i-n junctions, 125 Quercus suber, 539 R Rabbit pancreas endocrine tissue sections, 345 Rare earth elements, 222 RBS, 338, 345 Reactive multilayers, 54 Reference spectra, 491 Relativistic electron diffraction, 290 Reproducibility of immunostaining quantification, 353 Reproducible three-dimensional microstructure analysis, 130 Resin type and carbon coating, 197 Resistivity, 244 Resolution, 441 RF photoinjectors, 290 Rigid foam, 384 Ring patterns, 20 Rutherford backscattered ion image, 147 Rutile, 62 S SAED, 20 Sample preparation, 558 Sample preparation method for TEM, 558 Scanning electron acoustic microscopy, 314 Scanning electron microscopy, 2, 366, 422 Scanning/transmission electron microscopy, 213 Scanning transmission electron microscopy, 251 Scheelite, 222 SDD, 93 Secondary electron dopant mapping, 237 Secondary electron image, 147 Secondary electrons, 125 Selective permeability of fusarochromanone (FC101), 545 SEM, 147, 435 Semiconductor devices, 244 Semiconductors, 237 Shape memory, 62 Si(Li), 93 Si(Li) detector, 476, 484 Silica aerogel matrix using HREM, EDX, and EELS, 114 Silicon, 237 Silicon drift detectors, 231, 484 Silicon nitride, 204 Silver staining, 377 SIMS, 30 Simulation, 454 Single crystal, 435 Single-shot, ultrafast electron diffraction, 282 SOFC, 71 Solid angle, 93 Solid oxide fuel cell Ni-YSZ anode interconnectivity, 71 Solid state crystal growth, 435 Spatially-resolved EELS, 106 Specimen preparation, 15 Specimen preparation for TEM studies, 15 Spectroscopy, 222 Spherical, 441 Splanchnic circulation, 194 Squamous cell carcinoma, 353 STEM, 244, 441 STEM-EDXS, 46 STIM, 338, 345 Strontium-doped lead zirconate titanate thin films, 30 Strontium-doped PZT thin films, 30 Structural and chemical characterization of Yb2O3-ZrO2, 46 Structural dynamics, 323 Study of electron beam nanofabrication, 204 Suberin, 539 Surface modification, 62 Surface oxide, 62 Swiss Light Source, 166 Symposium on ultrafast electron microscopy, 271 Synchrotron radiation X-ray tomographic microscopy, 166 T 330 million year old charcoalified seed fern fertile organs, 166 3D, 71, 395, 441 Tannin, 384 Tannin-derived organic and carbon foams, 384 Technology advances on EDS system performance, 484 TEM, 20, 30, 62, 154, 435, 558 TEM contrast, 251 Tephritidae, 422 Texture, 20 Thin films, 15, 20 Three-dimensional, 244 Three-dimensional analysis, 71 Three-dimensional reconstruction, 377 Time-gated detection, 314 Time resolution, 272 Time-resolved acquisition technique, 106 Titanium nitride, 106 Tooth biomineralization, 154 Top-hat filter, 491 Tortuosity, 384 Transformed cells, 545 Transmission electron microscopy, 15, 251, 272 Two- and three-dimensional resolution, 441 Two-photon PEEM, 314 U Ultracold electron source, 282 Ultrafast, 290, 298 Ultrafast electron nanocrystallography, 323 Ultrafast imaging, 314 Ultrafast transmission electron microscopy, 272 Ultra-high voltage electron microscopy, 377 Ultrastructural observations, 539 Ultrastructure of the epithelial cells, 154 V Valence band, 125 Valence states, 36 Vascular, 194 W W